Identifikasi Bahaya Aktivitas Kerja Menggunakan Kaidah Hazard Identification, Risk Assesment And Risk Control (HIRARC) Pada Unit Mobile Crane di Departemen Penyewaan Alat Berat PT XYZ - Nasich, Muhammad Iqbal; Wasiur R, Akhmad; Dhartikasari Priyana, Efta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT XYZ is a subsidiary from one of the largest fertilizer companies in Indonesia which was only formed at the end of 2022 which was previously a compartment of its parent company. PT XYZ has several departments under it starting from the maintenance department, fabrication department, engineering and business department and also the ALBER (Heavy Equipment) department. Because it is a newly established company and with the addition of several new units, an OHS policy is needed for the safety of the company's work activities. Especially for the mobile crane units. The Hazard ldentification, Risk Assessment, and Risk ControI (HIRARC) procedure was apIicated in this study to minimaIized any kind of risk. Using the Job Safety AnaIysis (JSA) method at the Hazard ldentification stage in this study. The risks to the hazards that have been identified wiII be counted based  on likeIihood and severity, which wiII determine the Ievel of risk. Based on the risk assessment, potential hazards are categorized into 4 levels, namely low risk, medium risk, high risk and extreme risk. In carrying out the mobile crane rental business process activities, 11 work activities with low and medium risk were found. What is highlighted in this business process is the process of operating a mobile crane where almost all activities carried out by operating a mobile crane have a risk with the highest severity value. Given the high risks that exist in the process of operating a mobile crane, updates and controls must be carried out frequently. Because  if you not improve tooIs and work activity the danger will be increased. It is necessary to socialize the application of K3 policies regularly and continuousIy from the beginning to the end of the business process.